Komposisi Jenis Plankton Pada Musim Penangkapan Ikan Penja (Gobioidea sp) Di Muara Sungai Mandar - Chichilia Qaila Azzahrah Rahman; Moh. Tauhid Umar; Nita Rukminasari; Sahabuddin Sahabuddin (Tropical Fisheries Management Journal, 2020)
Penja is an endemic fish in the Mandar river and is one of the small pelagic fish species that has been used by fishermen in Polewali Mandar for a long time. Penja fish is one of the water organisms that utilize plankton as its food. This study aims to determine the composition of the plankton species the fishing season in Mandar waters of Polewali Mandar Regency, West Sulawesi Province. This research was conducted in November-December 2017. The sampling location was conducted in two different water locations which are at estuary and body of Mandar River, Polewali Mandar Regency, West Sulawesi Province. And the identification of samples was done at the Biology Laboratory of Plankton and Natural Feed at the Research Center for Brackishwater Aquaculture Development and Fisheries Extension (BRPBAP3) of Maros Regency. The results of this study indicate that the highest abundance of plankton during the fishing season in the estuary waters and the month of December. Bacillariophyceae class is the most plankton class found during the study and there is 37 genus plankton consisting of 28 genus of phytoplankton and 9 genus of zooplankton. The range of diversity index value during fishing time, sampling location, research month and sampling time are 1 <H '<3 which means medium diversity, uniformity index value is 0.7-0.9 so that the plankton uniformity index is relatively the same or equal, and the Domination index value indicates that no domain genus in the community.